2011
DOI: 10.1093/ndt/gfr429
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of HLA donor-specific antibodies detected by single antigen assay in kidney transplantation

Abstract: The presence of preformed HLA DSA in transplanted patients with a negative cytotoxicity crossmatch is associated with a lower allograft survival. The detection of anti-HLA with no DSA has no influence in the graft outcome. Finally, there were no demonstrable effects of mean fluorescence intensity (MFI) values >1500 on graft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 21 publications
4
61
1
1
Order By: Relevance
“…[12][13][14][15][16][17][18][19][20] These studies were excluded from our primary analysis. A quantitative analysis of this cohort (group 2) was limited to eight studies because adequate data could not be extracted from one of the studies identified for inclusion in this analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14][15][16][17][18][19][20] These studies were excluded from our primary analysis. A quantitative analysis of this cohort (group 2) was limited to eight studies because adequate data could not be extracted from one of the studies identified for inclusion in this analysis.…”
Section: Resultsmentioning
confidence: 99%
“…20 As was seen in the studies included in our primary analysis (group 1, negative flow crossmatch), all eight studies in group 2 (unknown flow crossmatch) were retrospective cohort studies in which the age of patients included with DSA-SPA was similar to the age of their comparative cohort without DSA in each individual study. [12][13][14][15][16][17][18][19] The types of donors included in these studies varied; three studies included only deceased-donor transplants, 14,16,18 one study included only living-donor transplants, 17 and four studies included both types of donors. 12,13,15 Induction regimens varied considerably across studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, investigators can detect very low concentrations of HLAdirected antibodies. In the last decade, numerous reports have addressed the methodological aspects, clinical relevance, and standardization of the Luminex SP SA assay for the detection of antibodies [53,54,[95][96][97][98][99][100] . The results of these studies have significantly expanded our understanding of anti-HLA antibody biology and the mechanism of the interaction between antibodies with antigens.…”
Section: Luminexmentioning
confidence: 99%
“…It is generally accepted that de novo developed DSAs represent a risk factor for graft failure even at low concentrations. The early detection of DSAs considerably reduces the incidence of antibody-mediated rejection (AMR) and transplant glomerulopathy [23,[51][52][53][54][55][56][57][58] . A posttransplant antibody analysis is a part of the routine monitoring of recipients.…”
Section: Introductionmentioning
confidence: 99%